Democratização da gestão pública: a municipalização da saúde nos municípios brasileiros de pequeno e médio porte - Bloch, Renata Arruda de (2000)
The present study analyses the relationship between Democracy and Local Government concerning Public Health Policy of small and medium Brazilian municipalities (with less than 50 thousand inhabitants). The management of the Department of Health in these municipalities was analysed to observe the democratization of public health through the main innovations on the way of management and on the health assistance. A comparison between the answers of the Health Department Managers of municipalities with less than 50 thousand inhabitants and the ones with more than 50 thousand inhabitants (collected in another research) was made as well as the elaboration of a factorial analysis model which verifies the relationship between Manage Profile, Innovating Management and Municipality Demographic Size. Innovating features are found in the small and medium municipalities although in a weaker degree than in the big ones. The relationship observed between the Demographic Extent and Innovating Management as well as the first and Manager Profile are not as strong as the Manager Profile and Innovating Management, concluding that the small dimension of a municipality is not an impediment to a more democratic health management.